Membangun Kebiasaan Cerdas Finansial pada Siswa Pondok Pesantren NW Montong Lisung melalui Edukasi Manajemen Keuangan - Mia Kurniati; Tutik Sukmalasari Putri; Sutriningsih Sutriningsih; Suharti Suharti; Rizky Maulana Raharja (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Low financial literacy among students, particularly in Islamic boarding schools, poses a challenge in fostering early economic independence. At Pondok Pesantren NW Montong Lisung, students generally lack the ability to manage pocket money, maintain financial records, and develop saving habits. This condition underlies the implementation of a community service program aimed at building smart financial habits through financial management education. The method employed a participatory approach consisting of counseling, training, and mentoring stages. Evaluation was conducted using pre-test and post-test, observation, and assessment of students’ financial record practices. The results showed a significant improvement in students’ financial literacy, increasing from an average of 42.5% to 79.5%, along with positive behavioral changes such as increased saving habits and better expense control. These findings indicate that financial management education is effective in improving students’ financial understanding and skills. Therefore, this program is important to be implemented sustainably to support the development of students’ economic independence in the future.